Sugar Ingenio Las Palmas del Chaco Austral: Scenario Changes in Regional Economic Etructure of the Sugar Sector - Picconi, Maria Lina (2011)
The Ingenio Las Palmas del Chaco Austral, locarcd in {he ciry L1s Palmas, Bermejo Dcparrmcnr, Chaco provincc in Argentina, was rhe most powerful irern of lha( country in ihe late S. XIX and any years of S. XX unril it closed its doors in rhe early '90s, moving fmm a narional capiralísm ro becomc wasteland, and directly ~ffecting {he dynarnic of social reproducrion of foróng dorncstic industries ro dcvelop a lICW organization of spacc and use resourccs to survive.